The impact of Private Higher Education staff performance management (PHE) in Surabaya, compensation, and competence on universities: Evidence from Indonesia - Wijaya, Oscarius Yudhi Ari (Goodwood Publishing, 2025)
Purpose: The purpose of this study is to investigate empirically the factors that influence university team member performance, such as pay and performance management systems, and also to compete. Methodology/approach: As part of this study's quantitative methodology, a questionnaire was given to staff members of Private Higher Education Institutions (PHEIs) in Surabaya, East Java. Results/findings: One of the essential tools to help universities navigate organizational procedures successfully is a performance management system. Since higher remuneration is perceived to result in better work outcomes, compensation plays a significant role in improving team member performance. Similarly, improving personnel competency has a positive impact on work outcomes. Performance management, compensation, and competency significantly impact team member performance in universities, including Indonesia. Research shows that adequate compensation and high competency can improve team performance. In addition, effective performance management also plays a role in enhancing team member motivation and Performance. Conclusions: Both theoretically and practically, this study contributes to the implementation of performance measurement systems, compensation structures, and competence development to improve university performance. Limitations: Performance is a current and expanding topic, debated by both practitioners and academic researchers, being a complex concept that can be defined from several perspectives. The development of a nation is greatly aided by Higher Education Institutions (HEIs), which raise the caliber of human resources. Contribution: The fundamental components of effective management strategies include team member satisfaction, goal achievement support, and clear communication.